2021
DOI: 10.1039/d0en00951b
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplastic sizes and numbers: quantification by single particle tracking

Abstract: Easy method to count and size plastic nanoparticles in water. A combination of sensitive fluorescence video microscopy, NileRed staining of plastic particles, and single particle tracking allows for counting and sizing nanoplastics.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…However, as the amount of plastic garbage generated increases, NP contamination in the environment may have an impact on the human community, as a whole. Recent studies have indicated the release of approximately 11.6 billion MPs and 3.1 billion NPs from a single plastic tea bag [ 42 ], at least 300 billion NPs/g from face scrubs [ 43 ], billions of NPs/mL (average size 160 nm) of water from polystyrene disposable cups [ 44 ], and an exposure of 14,600–4,550,000 MPs per capita per day from polypropylene infant feeding bottles [ 45 ], which are considered common sources of exposure to humans. The number of particles used for exposure in this study corresponds closely to the natural exposure of NPs in the human system; however, looking at the continuous exposure of NPs in the natural environment, these NPs may cause even more damage to human health than observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the amount of plastic garbage generated increases, NP contamination in the environment may have an impact on the human community, as a whole. Recent studies have indicated the release of approximately 11.6 billion MPs and 3.1 billion NPs from a single plastic tea bag [ 42 ], at least 300 billion NPs/g from face scrubs [ 43 ], billions of NPs/mL (average size 160 nm) of water from polystyrene disposable cups [ 44 ], and an exposure of 14,600–4,550,000 MPs per capita per day from polypropylene infant feeding bottles [ 45 ], which are considered common sources of exposure to humans. The number of particles used for exposure in this study corresponds closely to the natural exposure of NPs in the human system; however, looking at the continuous exposure of NPs in the natural environment, these NPs may cause even more damage to human health than observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 54 ] Otherwise, nanoparticle tracking analysis (NTA) consents imaging nanoplastics by recording the diffracted light from an incident laser and furnishes information on their size distribution, concentration, and Brownian diffusion. [ 55 ] It has been employed to examine the temporal fragmentation of disposable polystyrene (PS) coffee cup lid into nanoplastics. [ 56 ] NTA shows potential in exploring the nanoplastic removal ability of nano/microrobots.…”
Section: Measurement Techniques For Nano/microplastics Degradationmentioning
confidence: 99%
“…Another technique that can analyse stained plastics coupled with fluorescence microscopy is the single‐particle tracking, which allows the identification of the number and the size of nanoparticles. For example, Molenaar et al [86] . combined these two techniques to analyse commercially available PS beads with a nominal diameter of 400 nm, 200 nm, 100 nm and 40 nm and plastic particles obtained by grinding a commercially available disposable PS plastic cup into a powder with a commercial kitchen mixer.…”
Section: Stainingmentioning
confidence: 99%